Block level cloud data deduplication scheme based on attribute encryption - Wenting GE; Weihai LI; Nenghai YU (网络与信息安全学报)
Due to the existing cloud data deduplication schemes mainly focus on file-level deduplication.A scheme was proposed, based on attribute encryption, to support data block-level weight removal.Double granularity weight removal was performed for both file-level and data block-level, and data sharing was achieved through attribute encryption.The algorithm was designed on the hybrid cloud architecture Repeatability detection and consistency detection were conducted by the private cloud based on file labels and data block labels.A Merkle tree was established based on block-level labels to support user ownership proof.When a user uploaded the cipher text, the private cloud utilized linear secret sharing technology to add access structures and auxiliary information to the cipher text.It also updated the overall cipher text information for new users with permissions.The private cloud served as a proxy for re-encryption and proxy decryption, undertaking most of the calculation when the plaintext cannot be obtained, thereby reducing the computing overhead for users.The processed cipher text and labels were stored in the public cloud and accessed by the private cloud.Security analysis shows that the proposed scheme can achieve PRV-CDA (Privacy Choose-distribution attacks) security in the private cloud.In the simulation experiment, four types of elliptic curve encryption were used to test the calculation time for key generation, encryption, and decryption respectively, for different attribute numbers with a fixed block size, and different block sizes with a fixed attribute number.The results align with the characteristics of linear secret sharing.Simulation experiments and cost analysis demonstrate that the proposed scheme can enhance the efficiency of weight removal and save time costs.